DEVELOPMENT AND VALIDATION OF ZERO AND FIRST ORDER SPECTROPHOTOMETRIC METHOD FOR DETERMINATION OF OPIPRAMOL IN BULK AND PHARMACEUTICAL DOSAGE FORM - Khan, Fazil; Gurupadayya, Bm; Nasefa, Am; Prudhvi, Sai (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: Two simple, precise and accurate zero and first order spectrophotometric methods were developed and validated for the quantification of opipramol in bulk and tablet dosage form. Methods: The quantitative analysis of the drug was carried out using the zero order and first order derivative values were measured at 254 nm and 266 nm respectively. The estimation of the drug was carried out by regression equations with the standard solution. Results: Calibration graph was found to be linear r2 = 0.996 for zero order and r2 = 0.998 for first order derivative over the concentration range of 2-10 Âµg/ml. Precise (intra-day relative standard deviation [RSD] and inter-day RSD values < 1.0%), accurate (mean recovery = 100.77 %), specific and robust. No obstruction was observed from general pharmaceutical adjutants. Conclusion: The developed derivative methods can be utilized in its routine analysis opipramol in quality control division. Â 